How the Other Half Dies: Narrating Identities in Shelley Jackson’s Half Life (2006) - Sascha Pöhlmann (Current Objectives of Postgraduate American Studies)
Shelley Jackson’s first novel Half Life “(2006) creates a complex parallel world that is populated by Siamese twins who coexist with one-headed people. Using Brian McHale’s distinction of modernist and postmodernist fiction, this essay argues that the narrative strategies employed in Half Life“ conflate the epistemological and ontological, and thereby indicate one way of moving beyond postmodernism.